2009
DOI: 10.1038/embor.2009.247
|View full text |Cite
|
Sign up to set email alerts
|

Shaping the mitochondrion: mitochondrial biogenesis, dynamics and dysfunction

Abstract: The regulation of mitochondrial fusion/fission, respiratory chain complex assembly, mitophagy and mitochondrial‐ER contact sites have profound implications for human disease, which are explored in this report.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Mitochondria are highly regulated organelles whose function is tightly linked to the metabolic demands and health of a cell (Brooks et al, 2009;Shaw and Winge, 2009;Funk and Schnellmann, 2012;Kubli and Gustafsson, 2012). Mitochondrial function is necessary for normal cell and tissue function, and is critical in energy-dependent repair processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondria are highly regulated organelles whose function is tightly linked to the metabolic demands and health of a cell (Brooks et al, 2009;Shaw and Winge, 2009;Funk and Schnellmann, 2012;Kubli and Gustafsson, 2012). Mitochondrial function is necessary for normal cell and tissue function, and is critical in energy-dependent repair processes.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria are dynamic organelles that are continuously regenerated through the processes of biogenesis, mitophagy, fission, and fusion (Brooks et al, 2009;Shaw and Winge, 2009;Cho et al, 2010;Funk and Schnellmann, 2012;Kubli and Gustafsson, 2012). MB is the assembly of new mitochondria from existing mitochondria, occurring under basal conditions to replace damaged mitochondria, but is rapidly induced in response to both physiologic and pathophysiological stimuli, including sepsis, exercise, fasting, hypoxia, and cellular injury (Puigserver and Spiegelman, 2003;Tran et al, 2011;Kang and Li Ji, 2012;Wenz, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This area of research remains highly underexploited. In 2009, Shaw and Martin (40) analysed epigenetic changes at the growing epithelial tongue after full thickness punch biopsy skin wounding. They found that the PRC2 components Ezh2 and Eed, expressed in normal epidermis, were rapidly and stably downregulated even after complete reepithelialization and, concomitantly, histone demethylases Utx and Jmjd3, not highly expressed in normal epidermis, were transiently upregulated in early wounding.…”
Section: Epigenetic Changes At the Wound Edgementioning
confidence: 99%
“…This demethylase can then bind specific PcG target genes for their transcriptional activation (41). The brief expression of Utx and Jmjd3 after wounding (40) suggest that gene activators and their potential targets are tightly regulated to limit the extent of chromatin remodelling during the wound healing response.…”
Section: Epigenetic Changes At the Wound Edgementioning
confidence: 99%
See 1 more Smart Citation